REINTEPRATASI AYAT 120 SURAT AL BAQARAH DENGAN PENDEKATAN TOLERANSIF - Abdul Muiz Syaerozi (LPPM Institut Agama Islam Al-Hikmah Tuban, 2016)
Many people who believe that Islam is a religion that teaches tolerance values to his people. Theological argument which states Islam is a religion that teaches the values of tolerance to their communities they draw from a Quran and al-Hadith. in the Qur'an many verses that invites his people to be tolerant in religious life. There are at least eighteen verses that directly relate to the significance of the values of tolerance for religious life, among the letters terbeut is verse 30 of Surat al-Naml. Paragraph 120 surat al-Baqarah should not in tafsiri with the interpretations are loaded with cargo intolerance. Because, harfiyyah